COMPONENTS OF THE SOCIO-POLITICAL WORLDVIEW OF FUTURE TEACHERS - Khakkulov Komil Yusupovich (Web of Journals Publishing, 2025)
In this article, the modern educator aims to engage not only with children but also with the educational, cultural, and spiritual-educational upbringing of adults. In the Republic of Uzbekistan, it is approached as the main means of forming the spirituality of a harmoniously developed personality. Reflections are made on the basics of pedagogical methods for improving the socio-political worldview of future teachers.
Keywords: Pedagogy, worldview, improvement, socio-political, future teacher.